Trends in the application of multimetric indexes in Brazil: scienciometric analyses related to fish Fauna - Ticiani, Douglas; Bogoni, Raquel Fernanda; Eichelberger, Ana Cristina Algeri; Berlatto, Amanda Frigo; Medeiros, Gabriela; Delariva, Rosilene Luciana (Ciência e Natura, 2018)
The evaluation of biotic integrity through multimetric analysis of the attributes of fish fauna is recognized as an important tool for water management and conservation policies. In this sense, the present study sought to elucidate tendencies in the use of the most used metrics in multimetric indices (MMIs), based on the fish assemblage, in Brazil. An electronic search of the literature was carried out in indexing databases of periodicals. The criteria used for the selection of scientific articles were to be carried out in Brazilian territory and the use of MMI with fish. Of total, 51.9% of the studies were applied in streams, with no temporal pattern. The highest concentration of studies was observed in the southeast region. In all, 99 different metrics were used, highlighting attributes related to trophic, tolerance and species composition. There was a increment of specific metrics over the years and environments, with the exception of rivers. In comparison to other environments, streams had significantly different metrics. Difficulties in the MMI proposal in Brazil are linked to the selection of aspects that characterize the condition of a habitat before the diagnosis of the ecological components in the classification of the environmental quality.